1998
DOI: 10.1063/1.366928
|View full text |Cite
|
Sign up to set email alerts
|

Whiskers in indium tin oxide films obtained by electron beam evaporation

Abstract: Indium tin oxide thin films consisting mainly of whiskers have been deposited on glass by electron beam evaporation. Low deposition rates ͑35 Å/min͒ and substrate temperatures in the 120-400°C range were used. Morphology by scanning electron microscopy, crystal structure, energy dispersive analysis of x-rays, and x-ray photoelectron spectroscopy compositions, optical and conducting properties of films have been studied as a function of temperature of growth and further annealing in air. Whiskers associate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…The effect of tin incorporation into the In 2 O 3 lattice has already been discussed in [12][13][14][15]. As shown by X-ray photoelectron spectroscopy [13] on thin films, tin is solely incorporated as Sn 4+ .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The effect of tin incorporation into the In 2 O 3 lattice has already been discussed in [12][13][14][15]. As shown by X-ray photoelectron spectroscopy [13] on thin films, tin is solely incorporated as Sn 4+ .…”
Section: Discussionmentioning
confidence: 96%
“…With increasing tin concentration, the lattice constant increases again. According to [13,14] this suggests the incorporation of Sn 4+ in interstitial sites. It should be noted that according to [13], the electric conductivity as well as the charge carrier concentrations of thin films increases strongly up to 11 mol% SnO 2 .…”
Section: Discussionmentioning
confidence: 97%
“…For the investigated structures, in frames of the Drude model it is the SPR resonance linewidth that represents the measure of damping γ of the free-electron oscillations in the isolated Lorentz spherical cavity, with the dielectric function given by Equation (5). (5) ω p = ne 2 /m e is the plasma oscillation frequency of the electrons, with the free electron density n, the electron charge e and effective mass m e , and γ is the damping constant of electron motion. For bulk metals γ = γ bulk is related to the electrical resistivity of the metal and is supposed to include all microscopic damping processes arising from photons, phonons, impurities, and electron-electron interactions.…”
Section: Plasmonic Effectmentioning
confidence: 99%
“…[5] The application range of ITO covers optoelectronic devices such as organic light-emitting diodes, [13,14] solar cells, [15] and sensitive detectors dedicated to glucose, [16] hydrogen peroxide, [17] or DNA fragments. [18] The application capability of transparent conductive oxide materials stimulate increased research activity in this area and the growing commercial scale production observed recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation